ROADMAP TO IMPLEMENTATION AND MANAGEMENT OF INNOVATION IN THE BRAZILIAN CIVIL CONSTRUCTION INDUSTRY - Pires, Vinícius Rodrigues Silva; Simôes, Eliane Antonio; Cirani, Claudia Brito Silva; Ribeiro, Rosinei Batista (Seven Editora, 2025)
This study aims to develop a roadmap to be used by a small enterprise that operates in the civil construction sector for the implementation and management of innovation. Bibliometrics were used for the construction of the theoretical framework. The Design Science Research was used to create the proposed artifact and a single case study was used for roadmap validation, indicating practical propositions for companies of the same sector and size as well as theoretical suggestions for future studies. The proposed roadmap was developed from the analysis of the theoretical foundation, mainly in studies that defined similar artifacts. The application of this roadmap in a case study allowed verifying its potential for implementation and management of innovations in the enterprise studied. The roadmapping process generated a roadmap with organized and clear information for customers, suppliers, and employees of the enterprise. It also assisted in the research and selection of innovations to be implemented. Participants showed integration with the proposal and with the process and this integration remained even after the conclusion of the study. The proposed roadmap facilitated the implementation and management of innovations in terms of products, processes, organization, and marketing.DOI: https://doi.org/10.56238/sevened2024.037-192